FEATURES OF THE FORMATION OF THE COMPONENTS OF THE MECHANISM OF STATE-PARTNER INTERACTION OF SUSTAINABLE ENTREPRENEURSHIP - Dubina, Mykola I. (Journal of Strategic Economic Research, 2025)
The article substantiates the relevance and timeliness of the issues regarding the features of the formation of mechanisms of state-private interaction of sustainable entrepreneurship. It is determined that in the conditions of the restoration of Ukraine after the large-scale destruction caused by the war, the issue of resource mobilization becomes particularly relevant for the sustainable development of entrepreneurship. State-private interaction is presented as a key process of existing management mechanisms capable of ensuring the attraction of investments, modernization of infrastructure and improvement of the quality of public services of sustainable entrepreneurship. Analysis of the state of state-private interaction of sustainable entrepreneurship in the national economy made it possible to find out that the elements that make up the mechanism should organically fit into the market system in order to ensure the growth of the efficiency of farms while complying with environmental restrictions, requirements and the creation of a favorable, safe sustainable environment. The formation of public-private interaction of sustainable entrepreneurship according to the scenario approach is based on the orientation of business activities to meet demand within the framework of the interregional division of labor, characterized by the dominance of the service sector, as well as a complex of social, budgetary, environmental and other problems, the effective solution of which is largely related to the activation of sustainable entrepreneurship areas.